PELATIHAN TEKNIK DASAR SEPAK BOLA (PASSING, DRIBBLING DAN SHOOTING) DI PS. GANTHARI - Dwi Candra Setiawan; Sudarsono Sudarsono; Muhammad Syarir Budiono; I Putu Gede Erlangga Saputra; Muhammad Fajar Pradana Ningsubkan; Renaldi Felathiza Yulhan (JPM PAMBUDI, 2023)
The talent of soccer players in Indonesia is very promising, but the lack of attention and a good coaching process, especially from an early age, causes the development of Indonesian football to be less good. One of the best ways to develop soccer potential and talent is through a soccer school (SSB). Through SSB basic training in soccer will be provided to prospective soccer players properly. The purpose of this service is to provide training to early-aged SSB participants on basic training in playing soccer which includes passing, dribbling and shooting. This training was conducted for two months in PS. Ganthari City of Malang. The results of this dedication show a pretty good increase in terms of passing, dribbling and shooting PS students. Ganthari. Based on these results, it is suggested to continue to carry out basic soccer training in order to develop better Indonesian football.